1984
DOI: 10.1039/p19840001791
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of perfluoronitroxides with sulphur dioxide

Abstract: Manchester M60 I ODPerfluoro-2,5-diazahexane 2,5-dioxyl reacts with sulphur dioxide and with sulphur tetrafluoride to give the 1 : 1 cyclic adducts perfluoro(4,7-dimethyl-1,3-dioxa-2-thia-4,7-diazacycloheptane 2,2-dioxide) and perf I uoro (4,7d i methyl -1,3d ioxa -2tet raf I uorot h ia -4,7d i azacyclo hepta ne) , respectively. Per - fluoro( 4,7-dimethyl-l,3-dioxa-2-thia-4,7-diazacycloheptane 2,2-dioxide) which oxidises iodide ion to iodine at room temperature, is stable to hydrolysis by aqueous potassium hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The high performance of sulfamate esters in amination reactions and their propensity to form six-membered oxathiazinane products inspired our investigation of sulfamates fashioned from N -alkylhydroxylamines . Catalytic C−H insertion of such substrates affords unique [1,2,3,6]-oxathiadiazinane-2,2-dioxide heterocycles that can, in principle, be reduced to yield differentially protected 1,2-diamines . Rhodium-catalyzed intramolecular C−H insertion of ureas and guanidines also gives cyclic products, which may be ring-opened to furnish analogous diamine derivatives; however, hydrolysis of such heterocycles generally requires forcing conditions incompatible with other attendant functional groups. ,, …”
mentioning
confidence: 99%
“…The high performance of sulfamate esters in amination reactions and their propensity to form six-membered oxathiazinane products inspired our investigation of sulfamates fashioned from N -alkylhydroxylamines . Catalytic C−H insertion of such substrates affords unique [1,2,3,6]-oxathiadiazinane-2,2-dioxide heterocycles that can, in principle, be reduced to yield differentially protected 1,2-diamines . Rhodium-catalyzed intramolecular C−H insertion of ureas and guanidines also gives cyclic products, which may be ring-opened to furnish analogous diamine derivatives; however, hydrolysis of such heterocycles generally requires forcing conditions incompatible with other attendant functional groups. ,, …”
mentioning
confidence: 99%
“…Meanwhile, Smith et al reported the reaction of SO 2 and SF 4 with dioxyl 80 and obtained two heterocycles 82a and 82b ( Scheme 21 ) [ 119 ]. In neither case was a copolymer formed, something which differed from the results from the reaction of dioxyl 80 with tetrafluoroethene and hexafluoropropene in a previous report [ 113 ].…”
Section: Seven- and Larger-membered Heterocyclesmentioning
confidence: 99%
“…The lack of convenient methods for the preparation of 1,2-diamine derivatives, however, remains a problem in synthesis, complicated by an unavoidable reliance on serial functional group interconversion. The application of C–H amination technology for 1,2-diamine assembly can, in principle, streamline access to such structures. , Our efforts to delineate a general solution for preparing differentially substituted 1,2-diamines have led to the identification of a novel family of N-protected hydroxylamine sulfamates that react under the action of a dirhodium catalyst to give [1,2,3,6]-oxathiadiazinane-2,2-dioxide heterocycles . Herein, we describe the synthesis and unique properties of N -Troc-derived oxathiadiazinanes as masked 1,2-diamine equivalents.…”
mentioning
confidence: 99%